Interpreting human rights : narratives from refugee centers in Greece - Kolliniati, Maria-Artemis (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Kolliniati's groundbreaking book, Interpreting Human Rights: Narratives from Refugee Centers in Greece, challenges the notion that the interpretation and application of human rights primarily occur within the corridors of power in Strasbourg or official European institutions. It argues that such interpretation takes place in the grassroots settings of rural areas and neighborhoods, by actors who do not belong to the class of decision-making elites. Focusing on the Aegean islands as exemplary sites of the European refugee crisis, the book draws on research conducted among local actors, including mayors, municipal councillors, representatives of NGOs, and staff at refugee reception and identification centers. The book is divided into five distinctive sections: Methodology, Legal Framework and the Emergence of Hotspots, Empirical Research: Narratives of Local Actors, Local Narratives and Political Attitudes, and Glocalisation of Human Rights. The study explores the role of human rights in narratives surrounding refugee flows, categorizing responses according to various political theory approaches such as global liberalism, egalitarianism, communitarianism, and conservatism. By integrating applied political theory with localized human rights interpretations, this book offers actionable steps for addressing the challenges of migration in today's interconnected world. By amplifying the voices of those directly engaged with one of contemporary Europe's most significant challenges, Interpreting Human Rights will appeal to scholars of sociology, political theory, politics, and international law, particularly those interested in migration, human rights and refugee studies"--
Human rights and local level -- Empirical research : methodology and theoretical framework -- EU and national legal provisions about asylum seekers -- Hotspots mandate and the role of the EU -- Chios, Vial -- Cos, Pyli -- Leros, Lepida -- Lesvos, Moria until Sept. 2020 and Mavrovouni or Kara Tepe : introduction -- Samos, Vathy -- Partiality : communitarianism and conservatism -- Impartiality : global liberalism and egalitarian liberalism -- Limiting the interpretation of human rights -- Pushbacks -- Portraying the relationship between human rights and reception and identification centres (RICs) in Chios, Cos, Leros, Lesvos, Samos -- Human rights fulfilment at the local level : glocalisation and vernacularization of human rights through social justice and solidarity.
Keywords: Human rights -- Greece; Refugees -- Greece -- Social conditions; Refugees -- Legal status, laws, etc. -- Greece; LAW / Emigration & Immigration; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; SOCIAL SCIENCE / Emigration & Immigration